Big Data viewed through the lens of management fashion theory - Dag Øivind Madsen; Tonny Stenheim (Cogent Business & Management, 2016)
Big Data (BD) is currently one of the most talked about management ideas in the business community. Many call it the “buzzword of the day.” In books and media articles, BD has been referred to as a “revolution” and “new era.” There is lots of optimistic and upbeat rhetoric surrounding BD. This has led some to question whether BD is a hyped-up management fashion. In this paper, the BD phenomenon is viewed through the lens of management fashion theory. Management fashion provides an analytical lens which can be used to analyze the supply and demand side forces shaping the emergence and evolution of BD. The analysis shows that BD emerged in the late 1990s, gained momentum during the mid-2000s and legitimacy in the late 2000s, and enjoyed an almost meteoric rise in popularity in 2011 and 2012. Moreover, the analysis shows that BD currently is a very popular and highly contagious management idea exhibiting several hallmarks of a management fashion. At the same time, evidence suggests that it may be of a longer duration and not just another transient management fashion or fad. The findings have several implications for the study of the BD phenomenon and more generally, management and IT fashions.
Keywords: 650